Efektivitas Hand sanitizer Ekstrak Etanol Kulit Terung Ungu (Solanum melongena L.) Terhadap Bakteri - Muhammad Ridho Yuriadi; Mitha Mutia Nilam Sari; Muhammad Yuda Pratama; Tri Widia Irianti; Fini Noor Nazila (Husada Mahakam, 2022)
Hand sanitizer is used to clean or remove germs on hands. Hand sanitizer can be made using natural ingredients such as purple eggplant skin (Solanum melongena L.), because contains metabolites such as alkaloids and flavonoids that function as antibacterial. This study aims to determine the effectiveness of hand sanitizer of extract purple eggplant skin against bacteria on the hands. This type of research is a quasi-experimental research design with a pre-posttest only control group design consisting of 5 treatments with concentrations of 20%, 30%, 40%, 50%, and 60%. The research subjects consisted of 5 people who swab their palms before and after giving hand sanitizer and then counted the number of germs in CFU/cm2. In conclusion, the most optimal time and concentration of ethanol extract of purple eggplant hand sanitizer in killing bacteria were 10 minutes and a concentration of 20%.